Several Turán-Type Inequalities for the Generalized Mittag-Leffler Function. (5th August 2020) - Dou, Xiang Kai; Yin, Li; Lin, Xiu-Li
Abstract : In this paper, several Turán-type inequalities for the more generalized Mittag-Leffler function are proved. In addition, we also gave affirmative answers to two open problems posed by Mehrez and Sitnik.